THE CAUSE OF THE OCCURRENCE OF HUMAN TRAFFICKING IN WEST JAVA - K, Siti Nurbayani (Jurnal Civicus, 2015)
The cause of the occurrence of human trafficking in West Java region, which is very fundamental that is due to poverty and education. The second factor that is predominantly being the main reason why many of the victims of human trafficking originating from West Java, involving various elements. In addition, cultural factors and lifestyle has become a powerful driving force as the driving factor for teenagers and people who are in the country to move due to lack of land occupation, and factor in their place due to towing will work, there is a glimmer of hope in a better life than working in the place of origin.